Frequency of Post-Transplant Erythrocytosis in Patients with Live Related Renal Transplant - Rameez Chandio, Muhammad Shoaib, Raza Muhammad Jamro (Pakistan Journal of Medical & Health Sciences, 2023)
Background: It is commonly observed in the patients undergoing kidney transplant. The red cell mass increased in this condition but the plasma volume remain normal. It is characterized by the hematocrit levels equal to 51% or greater than 51%. Study design: It was a cross-sectional and descriptive study conducted at the department of nephrology and transplantation, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences Gambat. This study was conducted for the duration of six months from January 2022 to June 2022. Material and Methods: There were total 90 patients selected for the study. There were 35 patients in the control group and 55 patients in the Post-transplant Erythrocytosis patients group. The 25 out of 35 were male and 7 were females. The 17 out of 55 were male and 38 were females. Haemoglobin and Hematocrit was assessed retrospectively. Those with Hct > 51 was labelled as PTE. The study comprised of control group and PTE group having post erythrocytosis patients. The duration of dialysis of the patients was 12 and 13 months for control and PTE group respectively. Results: The red cell and plasma volume of the control group and PTE was analyzed and it showed that most of the patients had their RCV and PV in the normal range. However, there were 5 patients in control group and 15 patients in PTE group that had reported low level of RCV. The percentage of alive patients with functional graft was more in case of control (97%) as compared to PTE group (83%). Conclusion: The study was done to find the frequency of post-transplant Erythrocytosis among patients and control group. It was found that there were several risk factors that could possibly play role in causing the disease. The 21% of the patients were diagnosed with PTE. Keywords: Erthrocytosis, haematocrit, and haemoglobin.